Study on Estimation of Avoidable Yield Losses Due to Pod Blight in Soybean [Glycine max (L.) Merr.] - Umbon, Chandrika; Ao, N. Tiameren; Banik, Susanta; Neog, Pankaj; Sumi, Kavi; Chakruno, Pezangulie (International Journal of Economic Plants, 2023)
The present study was undertaken at School of Agricultural Sciences and Rural Development (SASRD) during 2021 July to October to estimate the avoidable yield losses due to pod blight. Cultural and morphological characterization of the pathogen causing pod blight disease in the crop was concluded. White mycelia growth was initially observed in potato dextrose agar media that later turned dark brown to black. Black, oval to conical acervuli, black setae longer than condiophores and hyaline, curved conidia were observed. Percent disease incidence, percent disease severity, yield (kg ha-1), and AUDPC were also recorded. Varieties as main plot factor and treatments as sub plot factor were laid out in Split plot design with three replications. Among all the combinations that were under study, moderately resistant variety (JS 97 52) with four numbers of foliar sprays recorded least disease incidence of 4.00% and least disease severity of 6.09%. Maximum (2326.67 kg ha-1) and minimum (1073.33 kg ha-1) yield was recorded from moderately resistant variety (JS 97 52) plot with four numbers of foliar sprays and control plot with susceptible variety, respectively. Least percent yield loss of 3.05% was observed from plots having moderately resistant variety with four foliar applications. Maximum avoidable yield loss of 37.96% was observed from susceptible plots with four foliar sprays. Maximum (256.27) and minimum (56.39) AUDPC has been observed from moderately resistant plots receiving four sprays and susceptible control plots respectively.